2011
DOI: 10.3858/emm.2011.43.3.021
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin glue increases the cell survival and the transduced gene product secretion of the ceiling culture-derived adipocytes transplanted in mice

Abstract: The development of clinically applicable scaffolds is important for the application of cell transplantation in various human diseases. The aims of this study are to evaluate fibrin glue in a novel protein replacement therapy using proliferative adipocytes and to develop a mouse model system to monitor the delivery of the transgene product into the blood and the fate of the transduced cells after transplantation. Proliferative adipocytes from mouse adipose tissue were transduced by a retroviral vector harboring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…They concluded that the most favorable combination for survival of bone marrow stromal cells was 20 mg/mL of fibrinogen and 87 NIH units/mL of thrombin, values intermediate between those of our control and low-low groups. The ratio of dead to total cells in our study was <30%, a finding consistent with previous reports 18,27 . Gugerell et al reported that thrombin concentrations of >400 NIH units/mL induced apoptosis of human keratinocytes 27 .…”
Section: Effect O F Fibrin F O R M U L At I O N O N T E N D O N R E Psupporting
confidence: 93%
See 2 more Smart Citations
“…They concluded that the most favorable combination for survival of bone marrow stromal cells was 20 mg/mL of fibrinogen and 87 NIH units/mL of thrombin, values intermediate between those of our control and low-low groups. The ratio of dead to total cells in our study was <30%, a finding consistent with previous reports 18,27 . Gugerell et al reported that thrombin concentrations of >400 NIH units/mL induced apoptosis of human keratinocytes 27 .…”
Section: Effect O F Fibrin F O R M U L At I O N O N T E N D O N R E Psupporting
confidence: 93%
“…The results of these reports have not been consistent, with some studies demonstrating that fibrin scaffolds increased cell viability, proliferation, or differentiation 18,20 and others showing that fibrin may adversely affect these parameters 16,18,20 . An in vitro tendon repair model showed that fibrin gel, acting as a carrier of growth differentiation factor-5 (GDF-5)-treated muscle-derived stem cells, enhanced tendon healing, as evaluated both mechanically and histologically, compared with a collagen gel at both two weeks and four weeks 21 .…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…In this study we isolated and cultured ADSCs in seven proliferation media as described by various authors (Katz et al 2005;Yoshimura et al 2006;Bunnell et al 2008;Du et al 2010;Zhou 2011;Aoyagi et al 2011;Frerich et al 2012) and two other proprietary media. Rate of proliferation is an important factor for clinical application, where autologous cells are required for reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose-derived stem cells (ADSCs) harvested from human adipose tissue provide an abundant potential source of multipotent adult stem cells (Rodbell 1964;Zuk et al 2001Zuk et al , 2002Du et al 2005;Katz et al 2005;Yoshimura et al 2006;Zhu et al 2008;Bunnell et al 2008;Tapp et al 2009;Du et al 2010;Maumus et al 2011;Aoyagi et al 2011;Zhou 2011;Sachs et al 2012). These can be harvested by minimally invasive procedures with a potential for diverse applications, such as studies in stem cell biology as well as clinical applications in regenerative medicine.…”
Section: Introductionmentioning
confidence: 98%